The darkness of the present : poetics, anachronism, and the anomaly - McCaffery, Steve (Tuscaloosa : University of Alabama Press, 2012)
This book includes essays that collectively investigate the roles of anomaly and anachronism as they work to unsettle commonplace notions of the "contemporary" in the field of poetics. In this book, a poet and critic argues that by approaching the past and the present as unified entities, the contemporary is made historical at the same time as the historical is made contemporary.
Cacophony, Abstraction, and Potentiality : The Fate of the Dada Sound Poem -- Corrosive Poetics : The Relief Composition of Ronald Johnson's Radi os -- Interpretation and the Limit Text : An Approach to Jackson Mac Low's Words nd Ends from Ez -- Transcoherence and Deletion : The Mesostic Writings of John Cage -- A Chapter of Accidents : Disfiguration and the Marbled Page in Laurence Sterne's The Life and Opinions of Tristram Shandy, Gentleman -- From Muse to Mousepad : Informatics and the Avant-Garde -- Parapoetics and the Architectural Leap -- "To Lose One's Way" (For Snails and Nomads) : The Radical Labyrinths of Constant and Arakawa and Gins -- Difficult Harmony : The Picturesque Detail in Gilpin, Price, and Clark Coolidge's Space -- The Pataphysics of Auschwitz -- The Instrumental Nightingale : Some Counter-Musical Inflections in Poetry from Gray to Celan.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Poetics; Literature -- Philosophy; Poétique.; LITERARY CRITICISM -- Poetry; Literature -- Philosophy; Poetics; Electronic book